SOCS1 insufficiency in systemic lupus erythematosus in a child: a case report - Cao, Lu; Wang, Qin; Zhang, Huating; Zhang, Jianjiang (Frontiers in Pediatrics, 2025)
This case report details a 6-year-old Han Chinese girl diagnosed with Systemic Lupus Erythematosus (SLE) associated with a frameshift variant in the SOCS1 gene. Initially presenting with fever and rash, the patient exhibited abnormal liver function, hypocomplementemia, and positive antinuclear and anti-dsDNA antibodies. Genetic testing identified a heterozygous frameshift mutation in the SOCS1 gene, inherited from her mother. The girl was treated with intravenous methylprednisolone, oral prednisolone, hydroxychloroquine, and mycophenolate mofetil, leading to significant clinical improvement. Considering the clinically relevant variant in SOCS1, the findings suggest that identifying pathogenic genes can facilitate the development of new therapeutic targets and biomarkers, with JAK inhibitors showing promise for treating SOCS1-related conditions.